Reflection of Hindu-Buddhist religious harmony in Nepali Temples - Ojha, Niranjan (Journal of Interdisciplinary Studies, 2021)
Religious harmony is essential for preserving harmony and peace in a multi religious nation like Nepal. If the issue of harmony is not resolved, there may be religious conflict in society. Although Nepal is a secular nation with a preponderance of Hindus, Buddhistsplay a significant and integral role in Nepalese society. They have coexisted in harmony with religion in Nepal. At this time, there were no religious conflicts or hostilities between Buddhists and Hindus. According to the Principle of Religious Syncretism, religious ideaswill be shared when two cultures come together and interact, with the dominant culture prevailing in the exchange. Syncretism of cultures and customs developed in Nepal for a number of reasons. Buddhism became a fundamental component of society due to its social acceptance and respect in the community. Buddhism is seen by Hindus as a part of Hindu philosophy, and vice versa. They have, however, made an effort to stand apart in recent years by religiously rejecting decades of harmony and peace. This study aims to examine the crucial elements fostering religious harmony in a multi-faith setting and how religious syncretism is reflected in Nepali temples. An in-depth interview and library research methods are used to study the issue of religious harmony. This article's goal is to examine the essential elements that support religious harmony in a multi-religious society as well as how religious syncretism is reflected in Nepalese temples. The causes of harmonic syncretism in the context of temples are also discussed in this study. The objective of this research is to create a longterm vision of religious peace between Nepal's Hindu and Buddhist communities. They might be motivated to keep healthy relationships by the findings.